ChemInform Abstract: Reactions of o‐Quinone Methides with Pyridinium Methylides: A Diastereoselective Synthesis of 1, 2‐Dihydronaphtho[2, 1‐b]furans and 2, 3‐Dihydrobenzofurans. Issue 41 (19th September 2013) - Osyanin, Vitaly A.; Osipov, Dmitry V.; Klimochkin, Yuri N.
Abstract This new method proceeds with complete diastereoselectivity giving the title compounds as trans‐isomers exclusively.